From ‘Nerve Fiber Regeneration’ to ‘Functional Changes’ in the Human Brain—On the Paradigm-Shifting Work of the Experimental Physiologist Albrecht Bethe (1872–1954) in Frankfurt am Main - Stahnisch, Frank W. (Frontiers in Systems Neuroscience, 2016)
Until the beginning 1930s the traditional dogma that the human central nervous system did not possess any abilities to adapt functionally to degenerative processes and external injuries loomed large in the field of the brain sciences (Hirnforschung). Cutting-edge neuroanatomists, such as the luminary Wilhelm Waldeyer (1836–1921) in Germany or the Nobel Prize laureate Santiago Ramón y Cajal (1852–1934) in Spain, debated any regenerative and thus “plastic” properties in the human brain. A renewed interest arose in the scientific community to investigate the pathologies and the healing processes in the human central nervous system after the return of the high number of brain injured war veterans from the fronts during and after the First World War (1914–1918). A leading research center in this area was the “Institute for the Scientific Study of the Effects of Brain Injuries,” which the neurologist Ludwig Edinger (1855–1918) had founded shortly before the war. This article specifically deals with the physiological research on nerve fiber plasticity by Albrecht Bethe (1872–1954) at the respective institute of the University of Frankfurt am Main. Bethe conducted here his paradigmatic experimental studies on the pathophysiological and clinical phenomena of peripheral and central nervous system regeneration.